Application of the Historical Burn Analysis Method in Determining Rainfall Index for Crop Insurance Premium Using Black-Scholes - Agus Sofian Eka Hidayat; Agnes Crycencia Sembiring (Journal of Actuarial, Finance, and Risk Management, 2023)
Indonesia is an agricultural country where rice sector has a high risk of production loss or crop failure. Agricultural Insurance is one of the government programs that helps farmers secure their farms. The aim of this final assignment is to obtain rainfall index to determine crop insurance premiums. The rainfall index is being carried out using Historical Burn Analysis which will produce exit values and trigger values for the index window January 2014 - December 2022 using secondary data from the Bali Climatology Station. In this study, Microsoft Excel 2016 was used as an application tool. The Black-Scholes method is used to calculate the premium in Jembrana Regency. The calculation of the rainfall index using the Historical Burn Analysis formula in determining agricultural insurance premiums using Black-Scholes can be used very well, the result show that the insurance premium value is very high where the lowest premium is IDR 6,654,075 and the highest premium is IDR 6,781,555.